Gamification, a successful method to foster leptospirosis knowledge among university students: a pilot study - Azhari, Nurul Natasya; Abdul Manaf, Rosliza; Ng, Shing Wei; Shakeeb Arsalaan Bajunid, Siti Farhana Bajunid; Mohamad Gobil, Abdul Rahman; Saad, Wan Zuhainis; Amin Nordin, Syafinaz (MDPI, 2019)
Leptospirosis is a zoonotic disease that has been reported in Malaysia and has been associated with a recent trend of recreational activities among the youth. Thus, efforts such as educational interventions among high-risk populations, especially the youth, are key to increasing public awareness regarding leptospirosis. This paper presents the findings of a pilot study wherein an educational intervention using a gamification intervention method was used to determine changes in leptospirosis knowledge among youth. On this note, students from a public university in Seremban district, Malaysia, were recruited and were asked to complete questionnaires before and after gamification activities. Baseline and immediate post-intervention data on leptospirosis knowledge were obtained. The total knowledge score was calculated, and differences in the mean pre- and post-intervention knowledge score were determined. Of the total 185 questionnaires that were completed at baseline and immediately post-intervention, only 168 that belonged to respondents who had heard of leptospirosis were analysed in this paper. A significant increase in leptospirosis knowledge was observed for the students following health education by gamification (p < 0.01). The results demonstrate the effectiveness of an educational intervention using gamification in improving leptospirosis knowledge among youth and suggest that gamification could become an efficient tool to prevent the disease within university-age demographics.